TAMI-43. IMPACT OF SEX AND RADIATION ON IRON TRAFFICKING IN BONE MARROW DERIVED MACROPHAGES. (9th November 2020) - Shenoy, Ganesh; Snyder, Amanda; Slagle-Webb, Becky; Marshall, Savannah; Schell, Todd; Chroneos, Zissis; Davalos, Dimitrios; Berens, Michael; Lathia, Justin; Barnholtz-Sloan, Jill S; Rubin, Joshua; Connor, James
Abstract: The tumor microenvironment in glioblastoma provides cancer cells with favorable conditions to proliferate and invade surrounding tissues. Macrophages comprise a large portion of the glioblastoma tumor microenvironment (TME) both in terms of volume and function. These cells have been reported to influence tumor progression by modulating immune responses, remodeling extracellular matrix, and providing nutrients to cancer cells among numerous other functions. Radiation therapy forms one of the pillars of glioblastoma management along with surgical resection and chemotherapy. Here we investigated the effects of radiation on macrophage iron metabolism. Using mouse bone-marrow-derived macrophages (BMDMs) we performed in-vitro 59 Fe radiotracer assays to study how radiation exposure modified iron trafficking in these cells. We found that low dose radiation at 0.25, 0.5, or 2 Gy from a 60 Co source stimulated iron release from the BMDMs with maximal release occurring at 0.5 Gy. Moreover, we observed that iron release was dependent on the amount of serum present in culture media with cells cultured in 20% fetal bovine serum (FBS) showing reduced iron release profiles compared to those cultured in 10% or 1% FBS. Since glioblastoma patients exhibit sexually dimorphic survival outcomes, we investigated whether these radiation-induced responses occurred in a sexually dimorphic pattern. At radiation doses of 0.25 Gy we observed that male macrophages tended to release more iron than female macrophages despite no differences in iron uptake between the sexes – raising the question as to whether differential iron trafficking in response to treatment contributes to the poorer survival outcomes observed in males. Our data suggest that delineating how supporting cells such as macrophages respond to glioblastoma treatment regimens may provide insights into addressing mechanisms of treatment resistance and further our understanding of the sexual dimorphism observed in patient outcomes.